Is politics art or science of governing? The abbreviated policy in the mirror of Plato and Aristotle - Quispe Arroyo, Adolfo (2019)
Politics is unavoidable in human activity being the highest degree of development of man in the polis. It is necessary to analyze politics as art or science in the pretense of guiding the group or the people towards happiness, which, by Aristotelian theoretical definition, is its end and the one who must govern is the Platonic virtuous man. In this case, those who should guide the people with what bases and philosophical discussions we are guided in this regard and if these qualities and / or virtues are possessed by our rulers. This analysis is done under the mirror of the parents of Western culture: Plato and Aristotle. The philosophers referred to have given theoretical bases of who or who should govern, prior development of certain virtues in the rulers. Whose supreme goal is to guide the happiness of the people who govern.